Contactless measurements of thermal conductivity and thermal diffusivity of full-size kern without samples optical characteristics alignment - E. Yu. Popov (Известия высших учебных заведений: Геология и разведка)
A new approach to the rock thermal property measurements with optical scanning method is presented in the article. The approach provides the numerous high precision non-destructive measurements on full size core samples and core plugs without special aligning optical coating on surface of the rock samples. Recently the coating was the obligatory requirement of the sample preparation and made this procedure sophisticated. The previous procedure could result in intractable alterations of the rock properties also. It is shown that the thermal diffusivity measurement quality does not suffer without special optical coating. The technique of rock thermal conductivity measurements is described which takes into account the various optical parameters of the investigated rock samples. The technique was realized for continuous profiling the rock thermal properties on full size cores without the special optical coating.